2022
DOI: 10.1002/jso.26857
|View full text |Cite
|
Sign up to set email alerts
|

Two‐ versus three‐field lymphadenectomy for esophageal cancer. A systematic review and meta‐analysis of early and late results

Abstract: This study aims to estimate whether prophylactic cervical lymphadenectomy for esophageal cancer influences the short-and long-term results through a systematic literature review and meta-analysis. Twenty-eight articles were selected in this systematic review, encompassing 9180 patients. Prophylactic neck lymphadenectomy for esophageal cancer should be performed with caution, as it is associated with worse short-term results compared to traditional two-field lymphadenectomy and does not improve long-term surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Third, other than pathological findings, differences in patient backgrounds may be a confounding factor. Lastly, although three-field lymphadenectomy has been widely performed for upper and middle thoracic esophageal cancer in Japan ( 23 ), its validity is debatable ( 23 - 25 ), and the external validity of this study is limited when considering that local effects cannot be excluded by surgical intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Third, other than pathological findings, differences in patient backgrounds may be a confounding factor. Lastly, although three-field lymphadenectomy has been widely performed for upper and middle thoracic esophageal cancer in Japan ( 23 ), its validity is debatable ( 23 - 25 ), and the external validity of this study is limited when considering that local effects cannot be excluded by surgical intervention.…”
Section: Discussionmentioning
confidence: 98%
“…It has been concluded that removing negative lymph nodes in secondary level lymph nodes will not improve disease control. On the other hand, a higher rate of intra- and postoperative complications have been observed after extended lymphadenectomy in different oncologic entities [ 13 , 14 , 15 ]. Based on such extrapolation from other entities, it seems appropriate to perform a systematic and careful lymphadenectomy in the primary nodes for proper staging and perform adjuvant therapies in case of any suspicion of microscopic systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative chylothorax is usually caused by injuries to the thoracic duct or to its tributaries during surgery [ 4 ] . Chylothorax may happen in several types of cardiothoracic surgery, including esophagectomy, lobectomy, cardiac procedures, and mediastinal tumors resection [ 5 , 6 , 7 , 8 , 9 ] . The diagnosis of chylothorax consists of evaluating triglyceride levels, cholesterol values, and microscopy crystals [ 10 ] .…”
Section: Introductionmentioning
confidence: 99%